2020
DOI: 10.1021/acs.jpcb.0c00441
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Disorder Drives Exciton Transfer in Tubular Chlorosomal Assemblies

Abstract: Chlorosomes stand out for their highly efficient excitation energy transfer (EET) in extreme low light conditions. Yet, little is known about the EET when a chlorosome is excited to a pure state that is an eigenstate of the exciton Hamiltonian. In this work, we consider the dynamic disorder in the intermolecular electronic coupling explicitly by calculating the electronic coupling terms in the Hamiltonian using nuclear coordinates that are taken from molecular dynamics simulation trajectories. We show that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…Moreover, they pointed at the distinct signature of a plastic crystal, a space filling mesophase that is closer to a real solid than, e.g., a liquid crystal. In particular, we found that the weak crystalline positional order is associated with a staggered rotation for each pigment along a distinct dynamic rotational degree of freedom within the confines of the assembly (Li et al, 2018(Li et al, ,2019(Li et al, ,2020, a feature that is increasingly considered to be essential for their function as an efficient antenna.…”
Section: Ll Open Accessmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, they pointed at the distinct signature of a plastic crystal, a space filling mesophase that is closer to a real solid than, e.g., a liquid crystal. In particular, we found that the weak crystalline positional order is associated with a staggered rotation for each pigment along a distinct dynamic rotational degree of freedom within the confines of the assembly (Li et al, 2018(Li et al, ,2019(Li et al, ,2020, a feature that is increasingly considered to be essential for their function as an efficient antenna.…”
Section: Ll Open Accessmentioning
confidence: 96%
“…The molecular motion in the strong confinement of the assembly is enhanced compared to the dynamics of proteins in a chiral structure, and more relevant for a fast excitonic transfer process. Including the unique role of correlated (classical) vibrations in producing (local) disorder and in driving non-adiabatic quantum-classical transfer is key to the calculation of electronic features, and often disregarded (Li et al, 2020). In addition for realistic in silico calculation of other emergent properties, this is a strict requirement (Frederix et al, 2018).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Given the variations in size, shape, and the number of aggregates within a single chlorosome, it is not surprising that these molecular assemblies feature a large degree of structural heterogeneity. As a consequence of this, structure determination by high-resolution X-ray crystallography is not feasible, and chlorosomes have been investigated by various combinations of other techniques including atomic force microscopy [ 10 , 11 , 12 ], solid-state NMR [ 13 , 14 ], optical spectroscopy both on ensembles [ 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and single-chlorosomes [ 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], cryo-electron microscopy [ 4 , 30 , 31 ], and computational approaches [ 6 , 32 , 33 , 34 ]. Nevertheless, details about their structural organization are still the subject of an ongoing debate.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a computational study was reported on chlorosomes using an approach resembling ours. 45 Complicating factors for the type of aggregates we consider, are that our amphiphilic dye molecules are considerably more challenging from an MD point of view than chlorophyll molecules; the situation is further complicated by the presence of solvated counterions in our systems.…”
Section: Conceptual Workowmentioning
confidence: 99%